“From the Lightest Light to the Darkest Dark” - Anette Svensson; Therése Haglind (Educare)
The present study focuses on consuming and producing stories using various forms of expression in the third-grade classroom. The aim of the study is to examine pupils’ and teachers’ experiences of working with a teaching unit that encourages the use of various text and media forms through literary productions, re-presentations, of Ronia, the Robber’s Daughter in order to gain increased insight into the pupils’ narrative competence and identity development. Hence, in what ways can working with various text and media forms and various forms of aesthetic expression promote pupils’ identity development?